PENERAPAN SISTEM PERAWATAN METODE ISMO PADA TURBIN TIPE VERTICAL FRANCIS KAPASITAS 35 MW - Arif Rochman Fachrudin (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2021)
The ISMO maintenance method is a maintenance method that is carried out when the machine performance has started to decline, the history of the machine is limited and there is a lack of information with the manual book. This method uses a reference degree of complexity to determine the scheduling. This maintenance method is applied to the Francis vertical type turbine with a capacity of 35 MW. The purpose of this study is to obtain maintenance information in the form of maintenance schedules and estimated maintenance costs of the francis vertical type turbine with a capacity of 35 MW. From this research, a comprehensive maintenance schedule and cost targets are produced, starting from inspection, small repair, medium repair and over-houle activities along with the amount of costs. In one cycle, inspection activities are carried out 9 times, medium repair 6 times and overhoule 1 time. The total cost required to maintain the turbine of vertical francis type for a period of 3 years is IDR 97.937.000,-